3D-look shading from contours and hatching strokes. (October 2015) - Bui, Minh Tuan; Kim, Junho; Lee, Yunjin
Abstract: In this study, we propose a novel and efficient method to generate 3D-look shade illustrations from simple sketches having outlines and hatching strokes. The basic idea is to use the contours and hatching strokes specified by a designer as a metaphor for constructing a normal field for 3D-look shading effects. The overall shape of a 3D object is depicted with contours, such as silhouette contours and feature contours related to geometric ridges and valleys. The shading effects are achieved by means of hatching strokes, which are usually along the principal directions of the object׳s local geometry. In our system, users first sketch an object׳s outline and can draw a set of hatching strokes over its interior regions. Next, the system estimates the 3D normals of the points on the contours and hatching strokes. A smooth normal field is then generated by interpolating the estimated normals with the diffusion processes. In addition, our system provides an intuitive method for adjusting normal transitions from edited to untouched regions using an alpha map. Finally, the texture coordinates of each pixel belonging to the drawn objects are computed based on the normal vector field so that the objects can be rendered in various 3D-look shadings, with changes for different materials and lighting. Experimental results show that our system can easily and effectively generate illustrations having 3D-look shading effects from various 2D sketches drawn by users. Abstract : Graphical abstract: Abstract : Highlights: Our system generates 3D-look shading illustrations from simple sketches with outlines and hatching strokes. Our system is the first study utilizing hatching strokes to construct surface normal from 2D hand-drawn input. Normal of each hatching stroke is approximated by automatically matching it with an arc of a 3D circle. We also propose a semi-automatic method to handle occluded regions that often appear in sketching.